Between evidence and allegation: factual accuracy in discussions on fluoride toxicity and research integrity - Andrea Buettner; Patrick Diel; Gerhard Eisenbrand; Bernd Epe; Petra Först; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; Michael Hellwig; Hans-Ulrich Humpf; Henry Jäger; et al. (Archives of Toxicology, 2026)

Evaluation in a porcine wound model and long-term clinical assessment of an autologous heterogeneous skin construct used to close full-thickness wounds - Nicholas Baetz; Pratima Labroo; Marytheresa Ifediba; Devin Miller; Kendall Stauffer; Michael Sieverts; Jessie Nicodemus-Johnson; Eric Chan; Ian Robinson; James Miess; Stephanie Roth; Jenny Irvin; et al. (Tissue and Cell, 2023)

Evaluation of the genotoxic potential of acrylamide: Arguments for the derivation of a tolerable daily intake (TDI value) - Sabine Guth; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Dirk Haller; Volker Heinz; Michael Hellwig; Jan G. Hengstler; et al. (Food and Chemical Toxicology, 2023)

Stellungnahme zu Acetaldehyd als Aromastoff: Aspekte der Risikobewertung - Jan G. Hengstler; Matthias Baum; Alexander T. Cartus; Patrick Diel; Gerhard Eisenbrand; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; et al. (Journal of Consumer Protection and Food Safety, 2022)
Opinion on acetaldehyde as a flavouring substance: considerations for risk assessment Acetaldehyde occurs naturally in many foods and is also used as a flavouring due to its fruity aroma. The International Agency for Research on Cancer (IARC) classified acetaldehyde as possibly carcinogenic to humans and, in combination with oral intake via alcoholic beverages, as carcinogenic to humans. Therefore, the question arises whether the use of acetaldehyde as a flavouring agent is still justifiable. The Senate Commission on Food Safety (SKLM) of the German Research Foundation (DFG) reviewed the scientific basis for health risk assessment of the use of acetaldehyde as a flavouring substance and adopted an opinion. Based on the available data, it is at present not possible to conclude if acetaldehyde is genotoxic and mutagenic in vivo after oral exposure. There is also uncertainty regarding the contribution of acetaldehyde as a flavouring substance to the overall exposure to acetaldehyde. Therefore, a science-based assessment on health risk related to the use of acetaldehyde as a flavouring is not possible at present. Considering the genotoxic potential as well as numerous data gaps that need to be closed for a full risk assessment, the SKLM is concerned about the safety of acetaldehyde as a flavouring substance. For reasons of precautionary consumer protection, the SKLM considers that the use of acetaldehyde as a food additive should be re-evaluated.

Salivary nitrate/nitrite and acetaldehyde in humans: potential combination effects in the upper gastrointestinal tract and possible consequences for the in vivo formation of N-nitroso compounds—a hypothesis - Gerhard Eisenbrand; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; Michael Hellwig; et al. (Archives of Toxicology, 2022)

Responses of Temperate Forests to Nitrogen Deposition: Testing the Explanatory Power of Modeled Deposition Datasets for Vegetation Gradients - Marina Roth; Hans-Gerhard Michiels; Heike Puhlmann; Carina Sucker; Maria-Barbara Winter; Markus Hauck (Ecosystems, 2021)
Eutrophication due to increased nitrogen concentrations is known to alter species composition and threaten sensitive habitat types. The contribution of atmospheric nitrogen deposition to eutrophication is often difficult to determine. Various deposition models have been developed to estimate the amount of nitrogen deposited for both entire regions and different landscape surface types. The question arises whether the resulting deposition maps allow direct conclusions about the risk of eutrophication-related changes in the understory vegetation composition and diversity in nitrogen-sensitive forest ecosystems. We combined vegetation and soil data recorded across eutrophication gradients in ten oligo-mesotrophic forest types in southwest Germany with datasets from two different deposition models specifically fitted for forests in our study region. Altogether, 153 forest stands, with three sampling replicates each, were examined. Linear mixed-effect models and NMDS analyses revealed that other site factors, in particular the soil C/N ratio, soil pH and canopy cover, played a greater role in explaining vegetation gradients than nitrogen deposition. The latter only rarely had effects on species richness (positive), nitrophyte cover (positive or negative) and the cover of sensitive character species (negative). These effects varied depending on the deposition model used and the forest types examined. No effects of nitrogen deposition on average Ellenberg N values were found. The results reflect the complex situation in forests where nitrogen availability is not only influenced by deposition but also by nitrogen mineralization and retention which depend on soil type, pH and (micro)climate. This context dependency must be regarded when evaluating the effects of nitrogen deposition.

Contribution to the ongoing discussion on fluoride toxicity - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2021)
Since the addition of fluoride to drinking water in the 1940s, there have been frequent and sometimes heated discussions regarding its benefits and risks. In a recently published review, we addressed the question if current exposure levels in Europe represent a risk to human health. This review was discussed in an editorial asking why we did not calculate benchmark doses (BMD) of fluoride neurotoxicity for humans. Here, we address the question, why it is problematic to calculate BMDs based on the currently available data. Briefly, the conclusions of the available studies are not homogeneous, reporting negative as well as positive results; moreover, the positive studies lack control of confounding factors such as the influence of well-known neurotoxicants. We also discuss the limitations of several further epidemiological studies that did not meet the inclusion criteria of our review. Finally, it is important to not only focus on epidemiological studies. Rather, risk analysis should consider all available data, including epidemiological, animal, as well as in vitro studies. Despite remaining uncertainties, the totality of evidence does not support the notion that fluoride should be considered a human developmental neurotoxicant at current exposure levels in European countries.

Toxicity of fluoride: critical evaluation of evidence for human developmental neurotoxicity in epidemiological studies, animal experiments and in vitro analyses - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2020)
Recently, epidemiological studies have suggested that fluoride is a human developmental neurotoxicant that reduces measures of intelligence in children, placing it into the same category as toxic metals (lead, methylmercury, arsenic) and polychlorinated biphenyls. If true, this assessment would be highly relevant considering the widespread fluoridation of drinking water and the worldwide use of fluoride in oral hygiene products such as toothpaste. To gain a deeper understanding of these assertions, we reviewed the levels of human exposure, as well as results from animal experiments, particularly focusing on developmental toxicity, and the molecular mechanisms by which fluoride can cause adverse effects. Moreover, in vitro studies investigating fluoride in neuronal cells and precursor/stem cells were analyzed, and 23 epidemiological studies published since 2012 were considered. The results show that the margin of exposure (MoE) between no observed adverse effect levels (NOAELs) in animal studies and the current adequate intake (AI) of fluoride (50 µg/kg b.w./day) in humans ranges between 50 and 210, depending on the specific animal experiment used as reference. Even for unusually high fluoride exposure levels, an MoE of at least ten was obtained. Furthermore, concentrations of fluoride in human plasma are much lower than fluoride concentrations, causing effects in cell cultures. In contrast, 21 of 23 recent epidemiological studies report an association between high fluoride exposure and reduced intelligence. The discrepancy between experimental and epidemiological evidence may be reconciled with deficiencies inherent in most of these epidemiological studies on a putative association between fluoride and intelligence, especially with respect to adequate consideration of potential confounding factors, e.g., socioeconomic status, residence, breast feeding, low birth weight, maternal intelligence, and exposure to other neurotoxic chemicals. In conclusion, based on the totality of currently available scientific evidence, the present review does not support the presumption that fluoride should be assessed as a human developmental neurotoxicant at the current exposure levels in Europe.

Low-dose photon irradiation alters cell differentiation via activation of hIK channels - Bastian Roth; Christine S. Gibhardt; Patrick Becker; Manuela Gebhardt; Jan Knoop; Claudia Fournier; Anna Moroni; Gerhard Thiel (Pflügers Archiv - European Journal of Physiology, 2015)

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

Characterization of a protein of the plastid inner envelope having homology to animal inorganic phosphate, chloride and organic-anion transporters - Christian Roth; Gerhard Menzel; Jean MacDonald-Comber Pettot; Sylvie Rochat-Hacker; Yves Poirier (Planta, 2004)

5-HT-like immunoreactivity in the brains of plethodontid and salamandrid salamanders ( Hydromantes italicus , Hydromantes genei , Plethodon jordani , Desmognathus ochrophaeus , Pleurodeles waltl ): an immunohistochemical and biocytin double-labelling study - Ursula Dicke; Markus Wallstein; Gerhard Roth (Cell and Tissue Research, 1997)

A model of the saccadic sensorimotor system of salamanders - Gerhard Manteuffel; Gerhard Roth (Biological Cybernetics, 1993)